Forecasting of the Volume of the SPA and Wellness Tourism Receipts in the South-West Bulgaria - Dimitrov, Preslav Mihaylov; Daleva, Diana; Stoyanova, Milena (Journal of Tourism, Sustainability and Well-being, 2017)
The present paper regards the application of some forecasting methods in regards to the SPA and Wellness tourism in South-West Bulgaria such as: the linear trend forecasting, the double exponential forecasting (the Holt’s method), the ARIMA method, the naïve method and the indexed naïve method. Specially designed model for estimation of the weight coefficient needed for determining the size of the sector of the SPA and Wellness tourism in the time series of the available data and in the forecast values is being presented. Future and past predictions have been achieved based on statistical records of a time series of 18-year periods. The present paper regards also several major problems in the application of the univariate forecasting methods for the purpose of the long-run forecasting of the volume of the tourism receives and especially the ones in the sub-sector of the SPA and Wellness tourism in South-West Bulgaria. These problems include as: (i) the problem of finding of a suitable general indicator; (ii) Determining the time series pattern, or the so-called “forecast profile” and selecting and using of suitable forecasting techniques; (iii) Calculating of short-run and long-run forecasts; (iv) comparing of the results of the forecast techniques on the basis of the errors in the forecasts; (v) Estimating the size of the SPA and Wellness tourism in South-West Bulgaria in certain terms, so that the forecast(s) of the above-mentioned general indicator could be particularized especially for regarded sub-sector and region. The results from the different forecasting methods and techniques are being presented and conclusions are drawn on the reliability of the achieved forecasts.